South-Pole directory: User's manual of the Directory of the Italian Research in Antarctica under the appointment of the Italian National Program for Antarctic Research - Biagioni, Stefania; Carlesi, Carlo; Carpen?, Andrea; Ramorino, Chiara; Rossi, Lucio; Schiarini, Silvia (1992)
In the 1989, following several reccomandations from International Institutions (like as the SCAR and the Antarctic Treaty) the Antarctic Project/ENEA (manager of the Italian National Program for Antarctic Research, PNRA) decided to set up a system for * the storing * the retrieval * the delivery of the data and the results from the italian expeditions in Antarctica. The project, called "South-Pole", is concieved as a network of interdisciplinary data-bases, each located in a specific 'field-center'. The realization of the overall project is still under way, but the first goal has been reached, and here it is described.